The moderating effects of physical activity on social anxiety and sleep disturbance: managing gaming disorder in young e-sports players - Serdar Solmaz; Mehmet İnan; Mustafa Yaşar Şahin (Frontiers in Public Health)
BackgroundInternet Gaming Disorder (IGD) has emerged as an increasing public health concern, particularly among adolescent and young e-sports players in recent years. The immersive and competitive nature of online gaming has been associated with an increase in mental health issues such as anxiety and insomnia among individuals with IGD. This study aims to examine the potential relationship between IGD, social anxiety, and insomnia, investigate the mediating role of social anxiety in this relationship, and explore the moderating role of physical activity in alleviating the negative effects of IGD.MethodsThe study involved 475 adolescent and young e-sports players aged 14–24, who typically engage in an average of 6 h of gaming per day. Participants completed the Internet Gaming Disorder Scale-Short Form, Social Anxiety Inventory, Insomnia Severity Index, and Physical Activity Frequency Question. Correlation and moderation analyses were used to examine the proposed relationships.ResultsThe findings revealed significant positive associations between IGD, social anxiety, and insomnia. Moreover, physical activity demonstrated a negative correlation with both social anxiety and insomnia. Notably, physical activity served as a moderator in the relationship between IGD and both social anxiety and insomnia, with higher levels of physical activity attenuating the adverse effects of IGD.ConclusionThis study illuminates the intricate relationship between IGD, social anxiety, and insomnia among adolescent and young e-sports players. The findings suggest that promoting physical activity may alleviate the negative psychological implications associated with IGD. These results provide important insights for the formulation of targeted intervention strategies aimed at this demographic.